Multivesicular bodies and their relationship with mitochondria in the rodent somatosensory cortex - Marta Turégano-López; Javier DeFelipe; Angel Merchan-Perez (Frontiers in Systems Neuroscience, 2015)
Multivesicular bodies (MVBs) are spherical organelles that are surrounded by a single membrane and contain small vesicles in their lumen. They are involved in degradation of cell components as an intermediary of the endosomal pathway. They also recycle cell components and are able to insert receptors in membranes that are far away from the neural soma. MVBs can fuse to plasma membrane and release exosomes that are essential for cell-to-cell communication. It has recently been described that MVBs store and transport damaged cargo from mitochondria and break it down by fusing with lysosomes. MVBs are also known to accumulate the protein aggregates that are involved in pathological conditions like Alzheimer’s disease and Parkinson disease. We used three dimensional electron microscopy with combined focused ion beam milling and scanning electron microscopy (FIB/SEM) to reconstruct MVBs in the rodent somatosensory cortex. We obtained ten stacks of serial sections from the neuropil of layer III. Using specifically developed software (Espina), we segmented and three-dimensionally reconstructed 678 MVBs. This revealed differences in their size and content (dark or clear vesicles). Some of them (7%) contained dark electron-dense laminar material in addition to the usual vesicles. We then classified MVBs based on their location. Our preliminary results indicate that MVBs located in dendrites outnumber those located on axons in approximately a 3:1 proportion. We also determined whether MVBs were related to other subcellular organelles, with special attention to mitochondria. We found that 19% were in contact with mitochondria. These MVBs are probably incorporating the damaged protein cargo contained in mitochondrial-derived vesicles, thereby acting as a defense mechanism that helps maintain normal mitochondrial function. The quantitative method that we have developed here will help determine the possible alterations of the endosomal pathway in pathological conditions.